Monetary co-operation in Europe - Gerhard Maier (Intereconomics, 1988)
The decisions of the EC conference in Nyborg last autumn were designed to consolidate and expand monetary integration in Europe. What degree of integration have the many years of effort achieved? What are the prospects for the future of the European Monetary System?
Keywords: 330; European Monetary System